EFEKTIFKAH METODA PEMBANTAIAN DAN VAKSINASI DALAM MENANGGULANGI RABIES DI BALI ? - Eka Dwipayana, I Made (Universitas Ahmad Dahlan, 2011)
Rabies is a fatal zoonotic viral disease caused by a virus which attacks the central nervous tissue. According to the World Health Organization (WHO), every year as many as 55,000 people die because they were infected by rabies virus. It is estimated as many as 95% of the incident occurs in Africa and Asia. Almost 99% of the transmission of rabies virus to humans is caused by dogs. It required some efforts to halt the spread of rabies. Some of which is by vaccination and culling the dogs. A mathematical model is required to analyze those efforts so that they became optimal when they applied to the field. Dogs population can be divided become two compartment as healthy (X) and infected dogs ( ). The model will be analyzed using linearization method to determine the characteristics of the population dynamics of healthy and infected dogs. To strengthen the analytical results, will be simulated using Runga-Kutta 4th order method. The result of the research showed that vaccination and culling methods are less effective in eradicating rabies, but by doing a certain level of vaccination and culling level of dogs, the eradicating of rabies spreading still can be done as long as it meets certain criteria.